Public beliefs and willingness to accept COVID-19 vaccines among adults in South-Western Nigeria: A cross-sectional study - Itse Olaoye; Aniebet Ekong; Abiona Samuel; Eirini Kelaiditi; Kyriaki Myrissa; Tsemaye Jacdonmi; Famokun Gboyega (AIMS Press, 2023)
Background: Despite the government's and development partners' unmatched efforts to ensure that every eligible person receives vaccinations, there have been concerns about vaccine fear, government mistrust, vaccine hesitancy and rejection expressed by the public, as well as various conspiracy theories involving the COVID-19 vaccines. This study assessed the public beliefs and willingness to accept COVID-19 vaccines and related factors among residents of Ondo State, Nigeria. Methods: Using a convenience sample technique, a cross-sectional survey of the adult population was carried out in the months of February and March of 2022. Factors influencing beliefs and willingness to accept COVID-19 vaccines were found by using univariate and multivariate statistical analysis. Results: 306 out of 323 respondents completed the survey and were included in the final analysis. The respondents mean age was 28.16 ± 16.2 years. Although n = 223, 72.9% of respondents reported to have received at least one dose of COVID-19 vaccines, (n = 205) 67.0% believed COVID-19 vaccines to be effective. Among the individuals who had not yet had any COVID-19 vaccinations, 2.6% (n = 8) of respondents were willing to accept the vaccines, whereas 14.1% (n = 43) were unwilling. Respondents' beliefs about the efficacy of COVID-19 vaccines were influenced by their gender, occupation, religion and educational attainment (p < 0.005). Conclusion: The study revealed a good level of positive beliefs about the vaccine, which was mirrored in vaccination history. However, those who had not yet received the vaccine were unwilling to do so, opening the door for more aggressive risk communication to be able to alter the course of events. In addition to addressing additional COVID-19 vaccination myths, we advise policy-makers to develop communication strategies that emphasise the safety of the COVID-19 vaccine. It is advised that all relevant stakeholders be included in government COVID-19 vaccination programmes by sharing timely, transparent information that fosters accountability.